2018
DOI: 10.1177/1077695817745464
|View full text |Cite
|
Sign up to set email alerts
|

Help Wanted: Realigning Journalism Education to Meet the Needs of Top U.S. News Companies

Abstract: Journalism programs working to stay current with industry practice often struggle to do so without forgoing traditional journalism skills and attributes. This longitudinal study involves content analysis of more than 1,800 jobs posted in either 2010 or 2015 by companies listed among the top 10 newspaper and broadcast journalism companies in the United States. The researchers found an increased demand for employee skills in social media and audience engagement, and a significant trend toward seeking candidates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 23 publications
2
41
0
2
Order By: Relevance
“…The initial coding sheet was adapted from previous studies (Carpenter, 2009;Massey, 2010;Wenger et al, 2018). To examine the validity of the coding sheet and confirm a consistent understanding among the coders, we conducted three rounds of pilot test and revised and finalized the coding scheme based on the results.…”
Section: Methods and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The initial coding sheet was adapted from previous studies (Carpenter, 2009;Massey, 2010;Wenger et al, 2018). To examine the validity of the coding sheet and confirm a consistent understanding among the coders, we conducted three rounds of pilot test and revised and finalized the coding scheme based on the results.…”
Section: Methods and Datamentioning
confidence: 99%
“…For example, a study of broadcast job ads identified previous work experience, writing skills, and personal qualities as the top three qualifications desired by broadcasters (Wenger & Owens, 2013). The increasing requirements of multimedia, big data, and social media publishing skills have also been found by the latest studies (Wenger et al, 2018).…”
Section: Identifying Journalistic Competencies Through Job Announcementsmentioning
confidence: 98%
“…This disconnect is especially sensitive, given the rapid pace of change within communications industries today (Ferrucci, 2018). To address this knowledge deficit, graduate students and faculty in media and communication education must constantly update their research and pedagogical approaches to align with the latest technological trends (Wenger et al, 2018). In addition to keeping up with industry advances, media and communication education stakeholders must also acquire a second type of occupational knowledge: understanding how their roles and responsibilities fit into the broader academic environment (Bogler & Kremer-Hayon, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A estos dilemas, se suman los recurrentes cuestionamientos a la educación periodística respecto a que, si bien los jóvenes profesionales poseen conocimientos teóricos y técnicos (Caminero y Sánchez, 2018), muchos de ellos carecen de las habilidades específicas para desenvolverse en las salas de redacción de los medios y agencias de noticias (Deuze, 2006). Y ello porque dichos espacios de trabajo requieren cada vez más a profesionales habituados a gestionar escenarios multimediales dominados por audiencias participativas, y capaces de desempeñarse en equipo y con plazos ajustados de entrega, según lo evidenciado recientemente por Wenger, Owens y Cain (2018).…”
Section: Introductionunclassified